2007
DOI: 10.1021/jf072457z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Persistence of Recombinant DNA of Roundup Ready Corn and Soybean in Rotation

Abstract: The presence of the recombinant cp4 epsps gene from Roundup Ready (RR) corn and RR soybean was quantified using real-time PCR in soil samples from a field experiment growing RR and conventional corn and soybean in rotation. RR corn and RR soybean cp4 epsps persisted in soil for up to 1 year after seeding. The concentration of recombinant DNA in soil peaked in July and August in RR corn and RR soybean plots, respectively. A small fraction of soil samples from plots seeded with conventional crops contained recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…leaves buried in soil did not persist for more than 4 months. Lerat et al (2007) reported that transgene DNA of GM corn and soybean was detected 7 months after the crop had been harvested but transgene DNA was not detectable after one growing season with conventional soybean in the same plots. However, Gebhard and Smalla (1999) detected transgene DNA from transgenic sugar beet (Beta vulgaris L.) in soil samples even 2 years after their introduction in a disposal site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…leaves buried in soil did not persist for more than 4 months. Lerat et al (2007) reported that transgene DNA of GM corn and soybean was detected 7 months after the crop had been harvested but transgene DNA was not detectable after one growing season with conventional soybean in the same plots. However, Gebhard and Smalla (1999) detected transgene DNA from transgenic sugar beet (Beta vulgaris L.) in soil samples even 2 years after their introduction in a disposal site.…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available about the potential of gene transfer in soil and the effect of indigenous bacteria carrying the transgenes on the structure and function of the soil microbial community (Dunfield and Germida 2004;Heinemann and Traavik 2004;Nielsen and Townsend 2004). As a prerequisite to addressing this issue, data on the persistence of transgene DNA in soil through continuous cultivation of GM crops need to be generated (Lerat et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, if plant-to-bacteria gene transfer occurs in field soil, it would be expected to occur during the growing season, as bacterial-populations peak, when soil temperatures and nutrient supply are optimal (Lerat et al, 2007).…”
Section: Introductionmentioning
confidence: 99%